MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PEMBAGIAN BILANGAN DENGAN PENGGUNAAN MEDIA ASLI PADA ANAK TUNARUNGU - Sri - Suyamti (Jurnal Penelitian Pendidikan Khusus, 2012)
This study originated from the problems of students with hearing impairment grade D III B do not understand the concept of the division of numbers, from the results of tests that researchers do, of the 10 questions are given only two numbers that are answered correctly, it rose not from the ideas of his own but due to chance alone original answer is correct, when the next time it was given back to the matter of students' answers had been right to be wrong, and a student again, learning should have mastered the basic division of numbers in the class D II. Therefore, researchers interested in improving deaf children's ability to understand the concept of sharing through the use of original media candy. This type of study is classroom action research conducted in collaboration with colleagues or classroom teacher. The subject of this study is a class D III B, two children with hearing impairment (KL, and RH). The study was performed in one cycle during the six sessions. Data were collected through observation, and tests given to children. The results showed the ability of children with hearing impairment to understand the concept of division is progressing by using the original media sugars in learning activities. The final results obtained by KL gain (80%), and RH obtained (100%). It can be concluded that the use of original media sugars can increase the ability of children with hearing impairment to understand the concept of division, it is advisable for teachers to be able to use the original media of candy to increase understanding of children in the division.